Dynamic Financial Inclusion in ASEAN 8: Do Macroeconomics and Financial Technology Matter? - Pandhit, Tunjung Sekar Laksmi (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to estimate the effects of macroeconomic indicators and financial technology on financial inclusion in ASEAN 8 during 2010-2018. There are three financial inclusion indicators, which include debit card ownership (Model 1), credit card ownership (Model 2), and domestic credit to GDP ratio (Model 3). Furthermore, the dynamic panel is applied to demonstrate dynamic financial inclusion models. The findings show that the domestic credit to GDP ratio is influenced by the unemployment rate, inflation, and financial technology. In addition, Model 1 and 2 show that the FEM is a robust model, while Model 3 indicates that REM is a robust model. This study encourages governments in ASEAN 8 to manage macroeconomic indicators progressively and stably to expand equal financial inclusion for the community